ANALYSIS OF CONNOTATION AND DENOTATION MEANINGS IN DAILY CONVERSATIONS OF TEENAGERS IN BAMBOO VILLAGE, SUB-DISTRICTUNA-UNA, TOJO UNA-UNA DISTRICT - Siti Hadija Alaydrus (PT. Anagata Sembagi Education, 2024)
This study explores the connotation and denotation meanings in adolescent conversations in Bamboo Village, Una-Una District, emphasizing the importance of understanding words to prevent miscommunication. Employing a qualitative descriptive method and a semantic approach, the research uses primary data collected directly through observation, listening, recording, and documentation. Data analysis involves reduction, presentation, and verification of oral conversations recorded in two settings: Bamboo Village's port and a residential yard. The findings reveal that teenagers frequently use connotative terms such as